Formation of germanium (Ge) – based waveguides for infrared application - Zhong, Jian (Nanyang Technological University, 2021)
Germanium-tin (Ge0.9Sn0.1) alloy is one of the complementary metal-oxide-semiconductor (CMOS) compatible materials in group-IV of the periodic table. Due to the large lattice mismatch between GeSn and Silicon (Si) substrate, the defects will generate within the GeSn layer. Currently, thin GeSn acts as a direct-band gap for near-mid infrared light source and photodetector. The report will show how to grow a high-quality single-crystalline GeSn (~1 μm) on germanium (Ge) buffer on Si substrate. The GeSn layer has low compression stress (-0.3%). A set of GeSn pedestal waveguide with a width of 1.25 μm has been fabricated. By measured the transmission power of GeSn at 3.74 μm, the results for propagation loss and bending loss are approximated to be 1.81 dB/cm and 0.19 dB/bend, respectively. Using infrared spectrometry, the GeSn waveguide is shown to have a transparency window to be longer than 25 μm.